THE ROLE OF THE WOMEN'S EMPOWERMENT AND CHILD PROTECTION SERVICE IN HANDLING VIOLENCE AGAINST CHILDREN - Nurul Pratiwi; Eka Fitra Ramadani; Yudhi Andrew Pratama Lumoindon (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The study aims to analyze the role of the Office of Women’s  Empowerment and Child Protection (DP3A) in handling cases of child abuse in Gowa Regency. The research employs a qualitative approach, with data collected through observation, interviews, and documentation. The focus of this study is to examine how DP3A carries out its role in addressing child abuse in Gowa Regency and to identify the inhibiting factors it faces in handling such cases. The findings reveal that DP3A Gowa Regency plays a strategic role in addressing child abuse through preventive measures such as community outreach and education, case handling through the UPTD PPA with legal and psychological services, and child recovery programs including counseling, therapy, and social reintegration. Collaboration with schools, the police, the Social Affairs Office, NGOs, and the establishment of a Children’s Forum further strengthens the child protection system in the region. However, the study also identifies several inhibiting factors, including a shortage of professional human resources, limited operational funding, and low public awareness influenced by patriarchal culture and the normalization of violence. These obstacles result in limited services, delays in case handling, and a large number of unreported cases. In conclusion, DP3A Gowa Regency plays an essential role in creating a comprehensive child protection ecosystem, although it still requires greater support in terms of human resource capacity, funding, and shifts in societal paradigms to ensure optimal child protection